ТАРИХИЙ ШАХСЛАР ОБРАЗИ ВА БАДИИЙ ТАЛҚИН (Гулистон Матёқубова ижоди мисолида) - Қурамбаева, Г. (SCIENCE and SOCIETY, 2018)
The article deals with the analysis of the skill of People’s poetess of Karakalpakstan G. Matyakubova in creating the images of historical figures.